OPTIMIZING MBKM MANAGEMENT BUSINESS PROCESSES AT XYZ HIGHER EDUCATION USING HARRINGTON - Cen, Li; Wang, Gunawan (Jurnal TAM (Technology Acceptance Model), 2024)
The MBKM program launched by the Ministry of Education and Culture in 2020 resulted in universities throughout Indonesia adding new business processes to process MBKM management, including XYZ College. One major problem occurred during the process, namely inefficiency in the business flow process, which caused the business process to run slowly. This research aims to help the MBKM central department reduce working days, make procedures more efficient, and synchronize data between the MBKM center and each study program. This research uses Harrington's Business Process Improvement (BPI) method, which eliminates errors, reduces waiting time, increases understanding, and makes it easy to use. The results of this research are recommendations for more efficient business processes with an efficiency of 33.95% in all MBKM center procedures based on simulation by Visual Paradigm Application.